On-the-run premia, settlement fails, and central bank access - Fabienne Schneider (Swiss National Bank, Study Center Gerzensee, 2024)
The premium on "on-the-run" Treasuries (i.e. the most recently issued ones) is an anomaly. I explain it using a model in which primary dealers hold inventories of Treasuries. Primary dealers are more likely to hold large inventories of on-the-run Treasuries. There is also less variation across primary dealers in the available stock of on-the-run Treasuries compared with all other, so-called off-the-run Treasuries. Because on-the-run Treasuries are easier to find, they trade at a premium. My theory is consistent with the USD 40 billion of Treasury contracts that fail to settle each day, with the median failure rate of off-the-run Treasuries being almost twice that of on-the-run Treasuries. I use the model to analyse the effects of granting access to central bank facilities to non-banks active in the Treasury market. Broad access stimulates trading and reduces the on-the-run premium, but settlement fails increase and, counterintuitively, only primary dealers benefit.
Keywords: 330; Government security; initial public offering; stock market price; bond market; USA; Staatspapier; Börsengang; Börsenkurs; Rentenmarkt; Theorie; USA